Basilar Artery Occlusion Chinese Endovascular Trial: Protocol for a prospective randomized controlled study. Issue 6 (July 2022) - Li, Chuanhui; Wu, Chuanjie; Wu, Longfei; Zhao, Wenbo; Chen, Jian; Ren, Ming; Yao, Chen; Yan, Xiaoyan; Dong, Chongya; Song, Haiqing; Ma, Qingfeng; Duan, Jiangang; et al.
Rationale: There are no randomized trials examining the best treatment for acute basilar artery occlusion in the 6–24-hour time window. Aims: To assess the safety and efficacy of thrombectomy for stroke due to basilar artery occlusion in patients randomized within 6–24 h from symptom onset or time last seen well. Sample size: For an estimated difference of 20% in proportions of the primary outcome between the two groups, 318 patients will be included for 5% significance and 90% power with a planned interim analysis after two-thirds of the sample size (212 patients) have achieved the 90 days follow-up. Methods and design: A prospective, multi-center, randomized, controlled, open-label and blinded-endpoint trial. The randomization employs a 1:1 ratio of mechanical thrombectomy with the detachable Solitaire thrombectomy device and best medical therapy (BMT) vs. BMT alone. Study outcomes: The primary outcome will be the proportion of patients achieving modified Rankin Scale (mRS) 0–3 at 90 days. Key secondary outcomes are: dramatic early favorable response, dichotomized mRS score (0–2 vs. 3–6 and 0–4 vs. 5–6) at 90 days, ordinal (shift) mRS analysis at 90 days, infarct volume at 24 h, vessel recanalization at 24 h in both treatment arms, and successful recanalization in the thrombectomy arm according to the modified thrombolysis in cerebral infarction (mTICI) classification defined as mTICI 2 b or 3. Safety variables are mortality at 90 days, symptomatic intracranial hemorrhage rates at 24 h, and procedure-related complications. Discussion: Results from this trial will indicate whether mechanical thrombectomy is superior to medical management alone in achieving favorable outcomes in subjects with acute stroke caused by basilar artery occlusion presenting within 6–24 h from symptom onset. Trial registration: URL:http://www.clinicaltrials.gov . ClinicalTrials.gov Identifier: NCT02737189.